PROSES PEMBUATAN ARTIKEL BERITA DI MEDIA SOSIAL VF DIGITAL INDONESIA - Aulya Nursafira (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) - Universitas Muhammadiyah Cirebon, 2021)
In a digital world, information and entertainment are easier to obtain. The widespread use of the internet and social media, now everyone can access information anytime and anywhere. Not only in the field of information and entertainment, in the field of marketing and advertising now everything is digital. The research was conducted at a digital company in Cirebon, VF Digital Indonesia. The formulation of the problem is how the process of making news articles at VF Digital Indonesia starts from searching for news to the uploading process on websites and social media. The manufacturing process has several stages that are not too long but require more attention. Starting from the search and topic determination, editing, then the upload process on the website and social media. This research uses observation, interviews and documentation research methods with a qualitative approach. Keywords: digital media, copywriting, news writing